Individualized patient decision-aid for immunosuppressive drugs in women with lupus nephritis: study protocol of a randomized, controlled trial. Issue 1 (December 2017) - Singh, Jasvinder; Shah, Nipam; Green, Candace
Abstract Background Systemic Lupus erythematosus (SLE), also commonly referred to as lupus, is a rare, but sometimes, fatal disease, that primarily affects young women. Lupus nephritis, a common manifestation of lupus, is more common and more devastating in patients of minority race/ethnicity. Patients have negative views of immunosuppressive drugs for lupus nephritis due to a concern about side effects and under-appreciation of its benefit. We designed a study to assess the effectiveness of individualized, computerized patient decision-aid for immunosuppressive drugs for lupus nephritis compared to a standard pamphlet for patient decision-making. Methods Adult women with lupus nephritis, with a current lupus nephritis flare or at risk of a future lupus nephritis flare will be randomized to individualized, computerized patient decision-aid for immunosuppressive drugs vs. standard pamphlet with information about lupus and its treatment including immunosuppressive drugs and outcomes. Patients will complete outcome assessments immediately after the intervention has been administered. Patients will be followed at 3-months with a brief survey, either in person or on the phone, and at 6-months with medical record review for exploratory outcomes. Co-primary outcomes are decisional conflict and informed choice regarding immunosuppressive drugs (combines values, knowledge and choice). Secondary outcomes include: (1) assessment of patient-physician communication by assessing audio-taped physician-patient communication after intervention administration; (2) concordance between patient's desired and actual role in immunosuppressive drugs decision-making using the control preference scale (CPS); and (3) patient perception of physician interaction using the interpersonal process of care- short form (IPC-SF). Discussion This is one of the first studies to evaluate the effectiveness of an educational intervention targeting minorities with lupus nephritis. This patient-centered lupus nephritis decision-aid will be available in the public domain in English and Spanish. Trial registration ClinicalTrials.gov Identifier:NCT02319525 ; registered on November 5, 2014.